Respuesta :

Answer:

12.25

Step-by-step explanation:

Expression

x^2 + 2y

x = 2.5

y = 3

x^2 = 6.25

2y = 3*2 = 6

x^2 + 2y = 6.25 + 6

x^2 + 2y = 12.25

Answer:

12.25

Step-by-step explanation:

We find the equation x^2 + 2y when x = 2.5 and y = 3.

We just have to replace x with 2.5 and y with 3 in the equation:

x^2 becomes 2.5^2

2y becomes 2 * 3 (When a variable is next to a number it means multiply)

So we get 2.5^2 + 2 * 3

We first do 2.5^2. 2.5^2 is the same as 2.5 * 2.5, which equals 6.25

Next we do 2 * 3 which equals 6

So it is 6.25 + 6, which is 12.25